Effect of Wisdom on Aggression and Decision Making Among Heads of Institutes - Dr. Sajid Mahmood Alvi; Ayla Khan; Hadiya Tariq (International Journal of Business and Economic Affairs, 2022)
The current study was designed to look into the effect of wisdom on aggression and decision-making among institute heads. Male and female (N = 200) heads of institutes’ were chosen for this study by using the purposive sampling technique. The wisdom of heads’ institutes was gauged by the Three-Dimensional Wisdom Scale (3D-WS), which was developed by Monika Ardelt in 2003. The General Decision-Making Questionnaire (GDMQ) was developed by Scott and Bruce (1995) to assess decision-making. Aggression was measured through Buss & Perry Aggression scale (BPAQ) developed by Buss in 1992. Descriptive statistics, alpha reliability, pearson correlation, and regression were computed to test the hypothesis. Pearson correlation showed a significant relationship between wisdom and decision-making and a negative relationship between wisdom and aggression. Uncertain decisions root anger among heads and ultimately affect the functioning of the education sector